2020
DOI: 10.1093/cdn/nzaa067_045
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6 Regulates Muscle Satellite Cell Function: A Novel Possible Role of Vitamin B6 in Muscle Regeneration

Abstract: Objectives So far, there is scarce information on potential roles of vitamin B6 (B6) in muscle regeneration. Thus, we examined if B6 has any effects on satellite cells (SCs), the muscle stem cells crucial for muscle regeneration. Methods Male ICR mice were divided into two groups receiving a B6 deficient level diet (1 mg pyridoxine (PN) HCl/kg diet) or a B6 supplement level diet (35 mg PN HCl) for 6 weeks (n = 6/group). Singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Thus, the upregulation of pyridoxine found in this study may also show a similar effect on myoblast differentiation, which indicated the potential of ginger in promoting skeletal muscle differentiation. In addition, this metabolite could regulate the function of muscle satellite cells together with the improvement of muscle regeneration by inducing proliferation and preventing apoptosis of satellite cells [73]. Deficiency of this metabolite will lead to the impairment of transcellular signaling between neurons and causes muscular convulsions, peripheral neuropathy and hyperirritability [74].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the upregulation of pyridoxine found in this study may also show a similar effect on myoblast differentiation, which indicated the potential of ginger in promoting skeletal muscle differentiation. In addition, this metabolite could regulate the function of muscle satellite cells together with the improvement of muscle regeneration by inducing proliferation and preventing apoptosis of satellite cells [73]. Deficiency of this metabolite will lead to the impairment of transcellular signaling between neurons and causes muscular convulsions, peripheral neuropathy and hyperirritability [74].…”
Section: Discussionmentioning
confidence: 99%